Critical thinking in cardiovascular imaging: hypertrophic cardiomyopathy and anterior mitral valve cleft - John, Thadathilankal-Jess; Bodenstein, Jo; Herbst, Philip (SA Heart Journal, 2021)
We present a case of a 72-year-old female with hypertrophic cardiomyopathy with systolic anterior motion (SAM) of the mitral valve and secondary mitral regurgitation (MR). The jet direction was noted to be centrally directed which is atypical for SAM associated MR. A search for a secondary cause revealed a mitral valve cleft at the A2/3 transition zone. This case highlights the importance of critical thinking in cardiovascular imaging.